2004
DOI: 10.1213/01.ane.0000132928.45858.92
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Allogeneic Blood Transfusion Use in Total Joint Arthroplasty

Abstract: Total joint arthroplasty (TJA) patients often receive allogeneic blood transfusion. In this study we sought to create and validate a clinical prediction rule for transfusion in TJA using data that are easily available when scheduling the procedure. Logistic regression modeling was applied to retrospective data from all TJA procedures performed in Edmonton, Alberta in 2000 (n = 1875). The area under the receiver operating curve for the resulting model in the training and validation data sets was 0.80 and 0.76 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 12 publications
6
58
1
Order By: Relevance
“…Identifying patients at increased risk of considerable perioperative blood loss and the need for perioperative blood transfusion is an important step toward establishing an effective blood management strategy 8 . Numerous studies have been performed to identify predictors of transfusion requirement in patients undergoing total joint arthroplasty [9][10][11][12][13] . However, only the role of preoperative hemoglobin as a predictor of transfusion requirement has been well defined 12 .…”
mentioning
confidence: 99%
“…Identifying patients at increased risk of considerable perioperative blood loss and the need for perioperative blood transfusion is an important step toward establishing an effective blood management strategy 8 . Numerous studies have been performed to identify predictors of transfusion requirement in patients undergoing total joint arthroplasty [9][10][11][12][13] . However, only the role of preoperative hemoglobin as a predictor of transfusion requirement has been well defined 12 .…”
mentioning
confidence: 99%
“…The net effect of these differences on transfusion risk can be estimated using data from another analysis of the 2000 TJA database. 11 We found that female gender increases the point odds of transfusion by 1.418; ASA III classification or greater increases it by 1.483; increasing body mass decreases it by 0.972Ákg -1 ; duration of surgery increases it by 1.017Ámin -1 ; and regional anesthesia reduces it by 0.729. Multiplying these effect sizes by the differences found between groups indicates that the net effect was to place Group S at higher risk, not lower risk, of transfusion.…”
Section: Discussionmentioning
confidence: 62%
“…The study's treatment algorithm itself served as the basis for subject selection. It was derived from the multivariate analysis of 1,875 TJAs performed in our region in 2000, 3 from which we determined that the three strongest determinants of allogeneic transfusion risk were hemoglobin concentration, body mass, and age. Neither the prediction rule nor the treatment algorithm allocated exactly equal weight to each of these three criteria, so we were not surprised to discover that our two groups differed in one of these three factors as well as in other respects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical records and anesthesia data sheets were reviewed and the following preoperative data were recorded: patient age, gender, diagnosis, medical comorbidities, American Society of Anesthesiologists (ASA) rating of operative risk (1-2, or C 3) [23], body mass index (BMI), and use of medications including iron and/or erythropoietin. Intraoperative data that were collected included anesthetic type, estimated blood loss, operative time, number of units of transfusion, preoperative and postoperative hemoglobin and hematocrit levels, procedure type, and implants used.…”
Section: Methodsmentioning
confidence: 99%